2021
DOI: 10.1111/scd.12657
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between periodontal disease and cognitive impairment in older adults of Korea

Abstract: Aims A potential association between the periodontal disease and cognitive impairment has been suggested, but the results are not yet conclusive. This study investigated the association between the two diseases. Methods and results This study included 140 individuals (M: 48, F: 92, average age: 77.2). For assessing cognitive ability, MMSE‐KC was used. The BGI index categorizes the periodontal disease based on important clinical parameters. In model 1 using the BGI index and the number of residual teeth as inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Growing evidence emphasizes the link between oral health and cognitive function in elderly people [ 4 6 ]. Indeed, many of the risk factors of systemic diseases, such as cardiovascular and circulatory diseases [ 7 9 ], rheumatoid arthritis [ 10 , 11 ], and Alzheimer’s disease [ 12 ], coincide with the ones of oral diseases [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence emphasizes the link between oral health and cognitive function in elderly people [ 4 6 ]. Indeed, many of the risk factors of systemic diseases, such as cardiovascular and circulatory diseases [ 7 9 ], rheumatoid arthritis [ 10 , 11 ], and Alzheimer’s disease [ 12 ], coincide with the ones of oral diseases [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the association with AD pathologies, studies have suggested that, by using model mice and postmortem brains, periodontal pathogens and their enzymes could promote the A␤ depositions and tau phosphorylation [28][29][30]. In humans, associations between the biofilm-gingival interface (BGI) index [31] and cognitive impairment have been reported in four studies [32][33][34][35]. Two of these studies indicated an association of the BGI index with the Mini-Mental State Examination (MMSE) score [34,35], while the others reported no such links [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, associations between the biofilm-gingival interface (BGI) index [31] and cognitive impairment have been reported in four studies [32][33][34][35]. Two of these studies indicated an association of the BGI index with the Mini-Mental State Examination (MMSE) score [34,35], while the others reported no such links [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis and cognitive impairment are problems that often occur in the elderly. Studies have shown a link between periodontitis and cognitive impairment [ 4 , 5 , 6 , 7 , 8 ]. Sung et al found that periodontitis was significantly correlated with impaired cognitive domains.…”
Section: Introductionmentioning
confidence: 99%